Circulating factors cause proteinuria in parabiotic zebrafish - Müller-Deile, J.; Schenk, H.; Schroder, P.; Schulze, K.; Bolaños-Palmieri, P.; Siegerist, F.; Endlich, N.; Haller, H.; Schiffer, Mario (Kidney International, 2019)
Proteinuria can be induced by impairment of any component of the glomerular filtration barrier. To determine the role of circulating permeability factors on glomerular damage, we developed a parabiosis-based zebrafish model to generate a common circulation between zebrafish larvae. A morpholino-mediated knockdown of a podocyte specific gene (nephronectin) was induced in one zebrafish larva which was then fused to an un-manipulated fish. Notably, proteinuria and glomerular damage were present in the manipulated fish and in the parabiotically-fused partner. Thus, circulating permeability factors may be induced by proteinuria even when an induced podocyte gene dysregulation is the initiating cause.
CRIS-Team Scopus Importer:2019-05-14
Keywords: nephrotic syndrome; podocyte; proteinuria